Ionic conductor, all-solid-state battery, and method for producing ionic conductor
The development of an ionic conductor with Li, P, S, and I, featuring a crystalline phase X and specific XRD peaks, addresses the low reduction resistance of LiBH4-P2S5-based conductors, enhancing their suitability for all-solid-state batteries by improving reduction resistance and stability.
Patent Information
- Application Number
- JP2022094978
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-06-13
AI Technical Summary
LiBH4-P2S5-based ionic conductors exhibit good ionic conductivity but have low reduction resistance, which limits their application in all-solid-state batteries.
An ionic conductor containing Li, P, S, and I with a crystalline phase X having specific XRD peaks at 2θ=29.1°±0.5° and 30.4°±0.5°, and a composition of (100-α){(1-β)LiBH4-βP2S5}-αLiI, where α and β are within specified ranges, is developed to enhance reduction resistance.
The new ionic conductor demonstrates improved resistance to reduction, making it suitable for use in the negative electrode layer of all-solid-state batteries, particularly when combined with Li or Li alloys, reducing reductive decomposition.
Smart Images

Figure 0007666411000002 
Figure 0007666411000003 
Figure 0007666411000004
Abstract
Description
Technical Field
[0001] The present disclosure relates to an ion conductor, a all-solid-state battery, and a method for manufacturing an ion conductor.
Background Art
[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has an advantage that simplification of a safety device is easy compared with a liquid-based battery having an electrolyte containing a flammable organic solvent. A solid ion conductor is used for the all-solid-state battery.
[0003]
[0002] Patent Document 1 discloses an ion conductor containing lithium (Li), borohydride (BH4 - ), phosphorus (P), and sulfur (S), and having a diffraction peak at a predetermined position in X-ray diffraction. Patent Document 2 discloses a compound represented by Li 7-x PS 6-x X x-z (BH4) z (wherein X is selected from the group consisting of Cl, Br, I, F, and CN, 0 < x ≦ 2, and 0 < z ≦ 0.50). Patent Document 3 discloses a method for manufacturing an ion conductor, which includes a step of mixing a raw material containing LiBH4 and P2S5 at a predetermined ratio with a solvent to obtain a mixture, and a step of removing the solvent from the mixture.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Patent Document 3
Summary of the Invention
Problems to be Solved by the Invention
[0005] For example, LiBH4-P2S5-based ionic conductors have good ionic conductivity, but tend to have low reduction resistance.
[0006] The present disclosure has been made in view of the above circumstances, and has as its main object to provide an ion conductor having good resistance to reduction. [Means for solving the problem]
[0007] [1] An ionic conductor containing Li, P, S, BH4, and I, and having a crystalline phase X which has peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in XRD measurement using CuKα radiation.
[0008] [2] The intensity of the peak at 2θ=29.1°±0.5° is I A The intensity of the peak at 2θ=30.4°±0.5° is defined as I B In this case, the above I A For the above I B Percentage of (I B / I A ) is 35% or more.
[0009] [3] Above I B / I A The ionic conductor according to [2], wherein the content of ionic charge is 60% or more.
[0010] [4] The ionic conductor according to any one of [1] to [3], having a composition represented by (100-α){(1-β)LiBH4-βP2S5}-αLiI, wherein the α satisfies 0<α≦20 and the β satisfies 0.01<β≦0.3.
[0011] [5] An all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer contains the ion conductor according to any one of [1] to [4].
[0012] [6] The all-solid-state battery according to [5], wherein the negative electrode layer contains the ion conductor.
[0013] [7] The all-solid-state battery according to [6], wherein the negative electrode layer contains Li alone or a Li alloy.
[0014] [8] A method for producing an ionic conductor, comprising: a preparation step of preparing an intermediate containing Li, P, S and BH4; an addition step of adding an I source to the intermediate to obtain a precursor; and a calcination step of calcining the precursor to obtain an ionic conductor having a crystalline phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in XRD measurement using CuKα radiation.
[0015] [9] The method for producing an ionic conductor according to [8], wherein the I source is LiI.
[0016]
[10] The method for producing an ionic conductor according to [8] or [9], wherein in the adding step, the precursor is obtained by amorphizing a mixture containing the intermediate and the I source. Effect of the Invention
[0017] The ionic conductor according to the present disclosure has an effect of having good resistance to reduction. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 2]1 is a flowchart illustrating a method for producing an ionic conductor according to the present disclosure. [Diagram 3] 1 shows the results of XRD measurement of the ionic conductor obtained in Example 1. [Figure 4] 1 shows the results of XRD measurement of the ionic conductor obtained in Example 2. [Diagram 5] 1 shows the results of XRD measurement of the ionic conductor obtained in Example 3. [Figure 6] 1 shows the results of XRD measurement of the ionic conductor obtained in Example 4. [Figure 7] 3 shows the results of XRD measurement of the ionic conductor obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The ionic conductor, the all-solid-state battery, and the method for producing the ionic conductor according to the present disclosure will be described in detail below.
[0020] A. Ionic Conductors The ionic conductor according to the present disclosure contains Li, P, S, BH4, and I, and has a crystalline phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in XRD measurement using CuKα radiation.
[0021] According to the present disclosure, the ion conductor has good reduction resistance because it contains a predetermined element including I. As described above, the LiBH4-P2S5-based ion conductor has good ion conductivity. This is because it has a crystal phase X, which will be described later. On the other hand, the LiBH4-P2S5-based ion conductor has low reduction resistance. This is presumably because the BH4 anion has low reduction resistance. In the present disclosure, an ion conductor having good reduction resistance is obtained by replacing a part of LiBH4 with, for example, LiI. The ion conductor in the present disclosure has good reduction resistance, and is therefore particularly useful as a material used in the negative electrode layer. In addition, when a part of LiBH4 is replaced with, for example, LiI, the structure of the crystal phase X is easily broken, but as described later, by using LiI after preparing an intermediate, it is possible to obtain an ion conductor having good reduction resistance while suppressing the breakage of the structure of the crystal phase X.
[0022] The ionic conductor in the present disclosure contains Li, P, S, BH4, and I. The ionic conductor is typically a LiBH4-P2S5-LiI-based ionic conductor. The ionic conductor preferably has a composition represented by (100-α){(1-β)LiBH4-βP2S5}-αLiI. α usually satisfies 0<α, may satisfy 1≦α, or may satisfy 5≦α. On the other hand, α usually satisfies, for example, α≦20, may satisfy α≦15, or may satisfy α≦10. β usually satisfies, for example, 0<β, may satisfy 0.01≦β, may satisfy 0.03≦β, or may satisfy 0.05≦β. On the other hand, β usually satisfies, for example, β≦0.3, may satisfy β≦0.25, or may satisfy β≦0.15.
[0023] The ionic conductor of the present disclosure includes a specific crystalline phase X. The crystalline phase X is presumed to be an argyrodite-type crystalline phase. In an X-ray diffraction (XRD) measurement using CuKα radiation, the crystalline phase X usually has peaks at 2θ=29.1°±0.5° and 30.4°±0.5°. The crystalline phase X may further have peaks at 2θ=14.4°±0.5°, 15.0°±0.5°, 24.9°±0.5°, 51.1°±0.5°, and 53.5°±0.5°. The positions of these peaks may be within the range of ±0.3° or ±0.1°, respectively.
[0024] In addition, the intensity of the peak at 2θ = 29.1° ± 0.5° is I A The intensity of the peak at 2θ = 30.4° ± 0.5° is I B Let us assume that A I B Percentage of (I B / I A ) is, for example, 35% or more, may be 50% or more, or may be 60% or more. B / I A is usually less than 100%.
[0025] The ionic conductor of the present disclosure preferably contains a crystalline phase X as a main phase. The "main phase" refers to a crystalline phase having a peak with the highest intensity in an XRD measurement using CuKα radiation. In addition, in an XRD measurement using CuKα radiation for the ionic conductor, a peak of LiI may or may not be observed.
[0026] The ionic conductor in the present disclosure preferably has high ionic conductivity. The ionic conductivity at 25° C. is, for example, 0.5×10 -3 S / cm or more, 1×10 -3 S / cm or more, and 2×10 -3 It may be S / cm or more.
[0027] The shape of the ion conductor may be, for example, particulate. The average particle size (D 50) is, for example, 0.1 μm or more and 50 μm or less. 50 ) can be obtained from the results of particle size distribution measurement by a laser diffraction scattering method. The use of the ion conductor is not particularly limited, but it is preferably used, for example, in an all-solid-state battery.
[0028] B. All-solid-state battery Fig. 1 is a schematic cross-sectional view illustrating an example of an all-solid-state battery according to the present disclosure. The all-solid-state battery 10 shown in Fig. 1 includes a positive electrode layer 1 containing a positive electrode active material, a negative electrode layer 2 containing a negative electrode active material, a solid electrolyte layer 3 formed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, a negative electrode current collector 5 that collects current from the negative electrode layer 2, and a battery case 6 that houses these members. Furthermore, at least one of the positive electrode layer 1, the negative electrode layer 2, and the solid electrolyte layer 3 contains the ion conductor described above in "A. Ion conductor".
[0029] According to the present disclosure, by using the above-mentioned ion conductor, an all-solid-state battery having good resistance to reduction can be obtained.
[0030] 1. Positive electrode layer The positive electrode layer in the present disclosure is a layer containing at least a positive electrode active material. The positive electrode layer may contain at least one of an ion conductor (solid electrolyte), a conductive material, and a binder in addition to the positive electrode active material.
[0031] The positive electrode active material may be, for example, an oxide active material. Specific examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4 and the like; and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0032] The surface of the positive electrode active material may be coated with a coating layer. This is because the reaction between the positive electrode active material and the solid electrolyte can be suppressed. Examples of materials for the coating layer include Li-ion conductive oxides such as LiNbO3, Li3PO4, and LiPON. The average thickness of the coating layer is, for example, 1 nm or more and 50 nm or less, and may be 1 nm or more and 10 nm or less.
[0033] The positive electrode layer in the present disclosure preferably contains the above-mentioned ion conductor. In addition, examples of the conductive material include carbon materials. Examples of the carbon materials include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the binder include fluorine-based binders such as polyvinylidene fluoride (PVDF). The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0034] 2. Negative electrode layer The negative electrode layer in the present disclosure is a layer containing at least a negative electrode active material. In addition to the negative electrode active material, the negative electrode layer may contain at least one of an ion conductor (solid electrolyte), a conductive material, and a binder.
[0035] Examples of the negative electrode active material include metal active materials and carbon active materials. Examples of the metal active material include Li, In, Al, Si, and Sn. The negative electrode active material is preferably Li alone or a Li alloy. Since Li alone or a Li alloy has a low reaction potential, a solid-state battery with a high voltage can be obtained. In addition, since the ion conductor in the present disclosure has good resistance to reduction, even when used together with Li alone or a Li alloy, reductive decomposition is unlikely to occur. The solid-state battery may be a battery that utilizes dissolution and deposition of Li as the negative electrode reaction. In this case, the solid-state battery may not have a negative electrode layer before the initial charge or after full discharge. On the other hand, examples of the carbon active material include mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, and soft carbon.
[0036] The ion conductor, conductive material, and binder are the same as those described above. The negative electrode layer in the present disclosure preferably contains the above-mentioned ion conductor. The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0037] 3.Solid electrolyte layer The solid electrolyte layer in the present disclosure is a layer containing at least a solid electrolyte. The solid electrolyte layer may contain a binder in addition to the solid electrolyte. The solid electrolyte layer in the present disclosure may contain the above-mentioned ion conductor as the solid electrolyte. The binder is the same as described above. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0038] 4.Other configurations The all-solid-state battery in the present disclosure generally has a positive electrode current collector that collects the positive electrode active material, and a negative electrode current collector that collects the negative electrode active material. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. In addition, a general battery case such as a SUS battery case can be used as the battery case.
[0039] 5.All-solid-state battery The all-solid-state battery in the present disclosure is preferably an all-solid-state lithium ion battery. The all-solid-state battery may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because it can be repeatedly charged and discharged, and is useful, for example, as an in-vehicle battery. The secondary battery also includes a secondary battery used as a primary battery (used only for one discharge after charging). The shape of the all-solid-state battery may be, for example, a coin type, a laminate type, a cylindrical type, or a square type.
[0040] C. Method for producing ionic conductors Fig. 2 is a flow chart showing a method for producing an ionic conductor according to the present disclosure. In Fig. 2, a mixture containing LiBH4 and P2S5 is amorphized and then calcined to prepare an intermediate (preparation step). Next, an I source (LiI) is added to the intermediate, and the mixture is amorphized to obtain a precursor (addition step). Next, the precursor is calcined to obtain an ionic conductor (calcination step).
[0041] According to the present disclosure, an ion conductor having better reduction resistance can be obtained by preparing an intermediate and then using an I source. Here, if a part of LiBH4 is replaced with an I source (e.g., LiI), the structure of the crystalline phase X is easily destroyed. In contrast, by preparing an intermediate and then synthesizing using an I source, it is possible to obtain an ion conductor having better reduction resistance while suppressing the destruction of the structure of the crystalline phase X.
[0042] 1. Preparation process The preparation step in this disclosure is a step of preparing an intermediate containing Li, P, S and BH4. The intermediate may be made by oneself or purchased from another party.
[0043] An example of a method for preparing an intermediate is a method in which a mixture containing a Li source, a P source, a S source, and a BH4 source is amorphized and then fired. An example of the Li source is Li sulfide. An example of the Li sulfide is Li2S. An example of the P source is P sulfide. An example of the P sulfide is GeS2. An example of the S source is elemental sulfur and the various sulfides described above. An example of the BH4 source is Li salt (LiBH4). In addition, it is preferable to appropriately adjust the composition of the mixture according to the composition of the desired ion conductor.
[0044] The method for making the mixture amorphous includes, for example, mechanical milling using a ball mill or a vibration mill. The mechanical milling may be a dry type or a wet type, but the latter is preferred from the viewpoint of uniform processing. The type of dispersion medium used in the wet mechanical milling method is not particularly limited.
[0045] Various conditions of mechanical milling are set so as to obtain a desired intermediate. For example, when using a planetary ball mill, the raw material composition and grinding balls are added and processed at a predetermined rotation speed and time. The rotation speed of the table of the planetary ball mill is, for example, 150 rpm or more, and may be 250 rpm or more. On the other hand, the rotation speed of the table of the planetary ball mill is, for example, 400 rpm or less, and may be 350 rpm or less. In addition, the processing time of the planetary ball mill is, for example, 30 minutes or more, and may be 1 hour or more. On the other hand, the processing time of the planetary ball mill is, for example, 30 hours or less, and may be 25 hours or less.
[0046] The amorphous mixture is fired to obtain an intermediate. The firing temperature is, for example, 150° C. or higher, and may be 180° C. or higher. Meanwhile, the firing temperature is, for example, 300° C. or lower. The firing time is, for example, 1 hour or higher, and may be 2 hours or higher. Meanwhile, the firing time is, for example, 10 hours or lower, and may be 5 hours or lower. The firing atmosphere can be, for example, an inert gas atmosphere or a vacuum.
[0047] Another example of a method for producing an intermediate is a method in which a mixture containing a Li source, a P source, a S source, and a BH4 source is fired (so-called solid phase method).
[0048] The intermediate contains at least Li, P, S and BH4. In addition, since an I source is added to the intermediate in the adding step described later, the intermediate does not need to contain I. That is, the intermediate does not need to contain I. On the other hand, a part of the I source may be contained in the intermediate in advance. In this case, the intermediate contains I. The ratio of I contained in the intermediate to I contained in the ion conductor is usually 50 mol % or less, may be 30 mol % or less, or may be 10 mol %.
[0049] The intermediate preferably has a crystalline phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in XRD measurement using CuKα radiation. The crystalline phase X is the same as that described above in "A. Ionic conductor," and therefore will not be described here.
[0050] 2. Addition process The adding step in the present disclosure is a step of adding an I source to the intermediate to obtain a precursor. An example of the I source is Li salt (LiI). The precursor may be a mixture containing an intermediate and an I source. The mixture is obtained by mixing the intermediate and the I source. On the other hand, the precursor may be an amorphous body containing the intermediate and the I source. The amorphous body is obtained by amorphizing a mixture containing the intermediate and the I source.
[0051] The method for making the mixture amorphous includes, for example, mechanical milling using a ball mill or a vibration mill. The mechanical milling may be a dry type or a wet type, but the latter is preferred from the viewpoint of uniform processing. The type of dispersion medium used in the wet mechanical milling method is not particularly limited.
[0052] Various conditions of mechanical milling are set so as to obtain a desired precursor. For example, when using a planetary ball mill, the raw material composition and grinding balls are added and processed at a predetermined rotation speed and time. The rotation speed of the table of the planetary ball mill is, for example, 150 rpm or more, and may be 250 rpm or more. On the other hand, the rotation speed of the table of the planetary ball mill is, for example, 400 rpm or less, and may be 350 rpm or less. In addition, the processing time of the planetary ball mill is, for example, 30 minutes or more, and may be 1 hour or more. On the other hand, the processing time of the planetary ball mill is, for example, 30 hours or less, and may be 25 hours or less.
[0053] The precursor may or may not have a crystalline phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in XRD measurement using CuKα radiation. In addition, peaks derived from the I source may or may not be observed in XRD measurement using CuKα radiation for the precursor.
[0054] 3. Firing process The calcination step in the present disclosure is a step of calcining the precursor to obtain an ion conductor having a crystal phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in XRD measurement using CuKα radiation. The calcination temperature is, for example, 150°C or higher, and may be 180°C or higher. Meanwhile, the calcination temperature is, for example, 300°C or lower. Also, the calcination time is, for example, 1 hour or higher, and may be 2 hours or higher. Meanwhile, the calcination time is, for example, 10 hours or less, and may be 5 hours or less. The calcination atmosphere may be, for example, an inert gas atmosphere or a vacuum.
[0055] 4. Ionic conductors The ionic conductor obtained by each of the above steps is the same as that described above in "A. Ionic conductor."
[0056] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0057] [Example 1] LiBH4 (Aldrich, 0.8022 g), P2S5 (Aldrich, 0.9096 g), and LiI (Kojundo Kagaku, 0.2882 g) were weighed. These were placed in a 500 ml ZrO2 pot, and further ZrO2 balls (450 g) with a diameter of 5 mm and heptane (100 g) were added and sealed. The sealed container was set in a ball mill (Fritsch P-5). A precursor was obtained by performing 20 sets of mixing at a rotation speed of 300 rpm for 1 hour and then pausing for 10 minutes. The obtained precursor was baked at 200 °C using a hot plate to obtain an ionic conductor. The composition of the obtained ionic conductor was 95 (0.9LiBH4-0.1P2S5)-5LiI.
[0058] [Example 2] An ionic conductor was obtained in the same manner as in Example 1, except that the amounts of the raw materials used were changed to LiBH4 (0.6915 g), P2S5 (0.7840 g), and LiI (0.5245 g). The composition of the obtained ionic conductor was 90(0.9LiBH4-0.1P2S5)-10LiI.
[0059] [Example 3] LiBH4 (4.0111g) and P2S5 (4.5478g) were weighed. These were placed in a 500ml ZrO2 pot, and further φ5mm ZrO2 balls (450g) and heptane (100g) were added and sealed. The sealed container was set in a ball mill (Fritsch P-5). The mixture was mixed at 300rpm for 1 hour, followed by a 10-minute pause, and this was repeated 20 times to obtain an intermediate. The obtained intermediate (1.7118g) and LiI (0.2882g) were placed in a 45ml ZrO2 pot, and further φ5mm ZrO2 balls (53g) and heptane (4g) were added and sealed. The sealed container was set in a ball mill (Fritsch P-5). The mixture was mixed at 300 rpm for 1 hour, followed by a 10-minute break, and this cycle was repeated 10 times to obtain a precursor. The resulting precursor was fired at 200°C using a hot plate to obtain an ionic conductor. The composition of the resulting ionic conductor was 95(0.9LiBH4-0.1P2S5)-5LiI.
[0060] [Example 4] Except for changing the amount of the intermediate to 1.4755 g and the amount of LiI to 0.5245 g, an ionic conductor was obtained in the same manner as in Example 3. The composition of the obtained ionic conductor was 90(0.9LiBH4-0.1P2S5)-10LiI.
[0061] [Comparative Example 1] An ionic conductor was obtained in the same manner as in Example 1, except that LiI was not used and the amounts of the raw materials were changed to LiBH4 (4.6865 g) and P2S5 (5.3135 g). The composition of the obtained ionic conductor was 90LiBH4-10P2S5.
[0062] [evaluation] (XRD measurement) X-ray diffraction (XRD) measurements using CuKα radiation were performed on the ionic conductors obtained in Examples 1 to 4 and Comparative Example 1. The results are shown in Figs. 3 to 7, respectively. As shown in Figs. 3 to 7, it was confirmed that the ionic conductors obtained in Examples 1 to 4 and Comparative Example 1 had a crystalline phase X having peaks near 2θ=29.1° and 2θ=30.4°. The intensity I A and the intensity of the peak around 2θ=30.4° I B Intensity ratio (I B / I A ) are shown in Table 1. For the intensity ratio, the straight line connecting the diffraction intensity at 2θ=23° and the diffraction intensity at 2θ=35° was used as the baseline.
[0063] (Ionic conductivity measurement) Ion conductivity measurements (25° C.) were performed on the ionic conductors obtained in Examples 1 to 4 and Comparative Example 1. Specifically, 100 mg of the powder of the obtained ionic conductor was sandwiched between two current collectors and placed in a ceramic cylinder under a pressure of 6 ton / cm. 2 The powder cell was pressed at room temperature to obtain the ionic conductivity from the resistance and thickness of the powder cell. The results are shown in Table 1.
[0064] (Li dissolution and precipitation test) A Li precipitation and dissolution test was carried out on the ionic conductors obtained in Examples 1 to 4 and Comparative Example 1. Specifically, 100 mg of the powder of the obtained ionic conductor was placed in a ceramic cylinder and subjected to a pressure of 6 ton / cm. 2 The powder was pressed at 400° C. to produce a green compact. Li metal foil was placed on each side of the green compact to produce an evaluation cell. A current of 0.1 mA was passed through the evaluation cell at room temperature for 1 hour. Then, a current of -0.1 mA (reverse current) was passed through the evaluation cell at room temperature for 1 hour. These operations were repeated for a total of 100 hours. The potential at the time of precipitation dissolution was compared between the initial potential and that after 100 hours, and the retention rate was calculated. The results are shown in Table 1.
[0065] [Table 1]
[0066] As shown in Table 1, it was confirmed that, in Examples 1 to 4, the ionic conductivity was low but the potential retention rate was high compared to Comparative Example 1. That is, it was confirmed that the ionic conductors obtained in Examples 1 to 4 have good reduction resistance. In particular, Examples 3 and 4 had good ionic conductivity compared to Examples 1 and 2. This is presumably because the collapse of the structure of the crystalline phase X was suppressed by the subsequent addition of LiI. [Explanation of symbols]
[0067] 1 … Positive electrode layer 2 … Negative electrode layer 3 … Solid electrolyte layer 4 … Positive electrode current collector 5 … Negative electrode current collector 6 … Battery case 10 … All-solid-state battery
Claims
1. Li, P, S, BH 4 and I, An ionic conductor having a crystalline phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in an XRD measurement using CuKα radiation, The ionic conductor has a composition represented by (100-α){(1-β)LiBH 4 -βP 2 S 5}-αLiI, The ionic conductor, wherein α satisfies 0<α≦20, and β satisfies 0.01<β≦0.
3.
2. The intensity of the peak at 2θ=29.1°±0.5° is expressed as I A The intensity of the peak at 2θ=30.4°±0.5° is defined as I B In this case, A The above I B The proportion of (I B / I A 2. The ionic conductor according to claim 1, wherein the ratio of ionic charge to total charge is 35% or more.
3. I B / I A The ionic conductor according to claim 2 , wherein the ionic conductor is 60% or more.
4. An all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, An all-solid-state battery, wherein at least one of the positive electrode layer, the negative electrode layer and the solid electrolyte layer contains the ionic conductor according to any one of claims 1 to 3.
5. The all-solid-state battery according to claim 4 , wherein the negative electrode layer contains the ion conductor.
6. The all-solid-state battery according to claim 5 , wherein the negative electrode layer contains Li alone or a Li alloy.
7. Li, P, S and BH 4 A preparation step of preparing an intermediate comprising: an adding step of adding an I source to the intermediate to obtain a precursor; a calcination step of calcining the precursor to obtain an ionic conductor having a crystalline phase X having peaks at 2θ=29.1°±0.5° and 30.4°±0.5° in an XRD measurement using CuKα radiation; A method for producing an ionic conductor having the above structure.
8. The method for producing an ionic conductor according to claim 7 , wherein the I source is LiI.
9. 9. The method for producing an ionic conductor according to claim 7 or 8, wherein in the adding step, the precursor is obtained by amorphizing a mixture containing the intermediate and the I source.
Citation Information
Patent Citations
LiBH4-LiI-P2S5 ternary composite solid electrolyte and preparation method thereof
CN112259786A
Solid electrolyte
JP2016134316A
Method for producing ion conductor
JP2018039689A
Solid electrolytes for lithium-ion electrochemical cells
JP2020534245A
All-solid-state lithium battery and its manufacturing method
JP2021515353A